The history of terrorism : from antiquity to ISIS - Chaliand, Gérard, 1934-; Blin, Arnaud (University of California Press, 2016)
This authoritative work provides an essential perspective on terrorism by offering a rare opportunity for analysis and reflection at a time of ongoing violence, threats, and reprisals. Some of the best international specialists on the subject examine terrorism's complex history from antiquity to the present day and find that terror, long the weapon of the weak against the strong, is a tactic as old as warfare itself. Beginning with the Zealots of the first century CE, contributors go on to discuss the Assassins of the Middle Ages, the 1789 Terror movement in Europe, Bolshevik terrorism during.